(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Choroid Plexus Papillomas (CPPs) is also known as benign but rare central nervous system(CNS) which affect the tufts of villi that make the ventricular system choroid plexus, which is responsible for production of cerebrospinal fluid(CSF). They make up between 0.5-1% in adult and 3-4% of paediatric group.Here we are introducing 11-year-old- female who visited with her parents in paediatric outpatient unit with the complaints of headache in the frontal region and backregion. She had 4-5 episodes of vomiting in previous week, she also developed the double vision since last 2 days. The patient underwent Magnetic Resonance Imaging of the brain and found the evidence of papilla enema in both eyes. Patient went to eye department for Vitreo-retained(VR) surgery. After that client was shifted to ward for the further management where she was administered the appropriate paediatric dose of antiedema and antiepileptic medication and other supportive measures. After treatment, the patient's condition was improved than before. Symptoms such as blurred vision relieved after surgery. These tumours rarely develop in children’s third ventricles, fourth ventricles or CP angle.